2010
DOI: 10.1287/opre.1090.0728
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Entrenched Insurgents

Abstract: During counterinsurgency operations, government forces with superior firepower confront weaker low-signature insurgents. Under what conditions should government (Blue) forces attack insurgent (Red) strongholds? How should the government allocate its force across different strongholds when the insurgents' threat to the Blue civilian population must be taken into account? How should the government respond to "smart" insurgents who anticipate the government's optimal plan of attack and prepare accordingly? How do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 11 publications
0
17
2
Order By: Relevance
“…Operations research originated from the efforts of military applications during World War II but has been widely resumed with respect to homeland security after September 11, 2001(Brown, Carlyle, Salmeron, & Wood, 2006Hu, Homem-de Mello, & Mehrotra, 2011;Kaplan, Kress, & Szechtman, 2010;McLay, Jacobson, & Nikolaev, 2009;Wright, Liberatore, & Nydick, 2006). Among different techniques of operations research, game theory is a popular tool to capture the strategic interactions between the terrorists and the government on resource allocation problems among multiple targets (Cox, 2009;Hall, 2009;Hausken, 2002;Insua, Rios, & Banks, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Operations research originated from the efforts of military applications during World War II but has been widely resumed with respect to homeland security after September 11, 2001(Brown, Carlyle, Salmeron, & Wood, 2006Hu, Homem-de Mello, & Mehrotra, 2011;Kaplan, Kress, & Szechtman, 2010;McLay, Jacobson, & Nikolaev, 2009;Wright, Liberatore, & Nydick, 2006). Among different techniques of operations research, game theory is a popular tool to capture the strategic interactions between the terrorists and the government on resource allocation problems among multiple targets (Cox, 2009;Hall, 2009;Hausken, 2002;Insua, Rios, & Banks, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jenelius et al (2010) analyze the impact of the degree of attacker information asymmetry on the likelihood of an attack and show that a less-informed attacker may cause more damage to a defender. Kaplan et al (2010) also consider the uninformed attacker setting and characterize a simple rule for the attacker's optimal strategy.…”
Section: Related Literaturementioning
confidence: 99%
“…Similarly to [3], Kaplan et al [31] use modified Lanchester models to study the force allocation problem of both the government and the insurgents and, using a sequential force allocation game between the two sides, obtain an equilibrium. It is shown that the insurgents' optimal strategy depends on the government level of situational awareness; when the government has perfect intelligence, in equilibrium the insurgents concentrate their force in a single stronghold that the government either attacks or leave unengaged, depending upon the resulting casualty count.…”
Section: Confronting Entrenched Insurgentsmentioning
confidence: 99%